A controlled study of sensory tics in Gilles de 1a Tourette syndrome and obsessive-compulsive disorder using a structured interview. Issue 2 (February 1997) - Chee, K Y; Sachdev, P
Abstract : OBJECTIVE: To determine the prevalence and characteristics of sensory tics in the Gilles de la Tourette syndrome (GTS), and a matched population of patients with obsessive-compulsive disorder (OCD) using a structured assessment. METHODS: 50 subjects each of GTS, OCD, and healthy controls were studied to determine the prevalence and phenomenology of sensory tics, and diagnose tic disorders, OCD, and affective disorders according to DSM-III-R criteria. The severity of tics and obsessive-compulsive symptoms were quantified using the Tourette syndrome global scale (TSGS) and Yale-Brown obsessive-compulsive scale (Y-BOCS) respectively. RESULTS: The GTS group (28%) had significantly-greater life-time prevalence of sensory tics than the OCD (10%) and healthy (8%) groups (P < 0.05). The sensory tics in both the GTS and OCD groups were predominantly located in rostral anatomical sites. Multiple sensory tics occurred in some patients with GTS or OCD, but not in healthy subjects. Within the OCD group, those who had sensory tics had significantly higher TSGS scores (P < 0.0001), and a higher prevalence of GTS (P < 0.005). CONCLUSIONS: Sensory tics seem to be a common and distinctive feature of GTS and that subpopulation of patients with OCD predisposed to tic disorders. Neurophysiologically, a possible explanation for sensory tics is that they represent the subjectively experienced component of neural dysfunction below the threshold for motor and vocal tic production.